Developmental abnormalities in the cornea of a mouse model for Marfan syndrome. (May 2020) - Feneck, Eleanor M.; Souza, Rodrigo B.; Lewis, Philip N.; Hayes, Sally; Pereira, Lygia V.; Meek, Keith M.
Abstract: Elastic fibres provide tissues with elasticity and flexibility. In the healthy human cornea, elastic fibres are limited to the posterior region of the peripheral stroma, but their specific functional role remains elusive. Here, we examine the physical and structural characteristics of the cornea during development in the mgΔ loxPneo dominant-negative mouse model for Marfan syndrome, in which the physiological extracellular matrix of its elastic-fibre rich tissues is disrupted by the presence of a dysfunctional fibrillin-1 glycoprotein. Optical coherence tomography demonstrated a reduced corneal thickness in the mutant compared to wild type mice from embryonic day 16.5 until adulthood. X-ray scattering and electron microscopy revealed a disruption to both the elastic fibre and collagen fibril ultrastructure in the knockout mice, as well as abnormally low levels of the proteoglycan decorin. It is suggested that these alterations might be a result of increased transforming growth factor beta signalling. To conclude, this study has demonstrated corneal structure and ultrastructure to be altered when fibrillin-1 is disrupted and has provided insights into the role of fibrillin-1 in developing a functional cornea. Highlights: mgΔ loxPneo mice showed abnormalities in corneal thickness from embryonic development through to adulthood. Elastic fibres were evident from E16.5 in both the WT and mgΔ loxPneo mouse corneas. Adult mgΔ loxPneo mouse corneas exhibited a disorganised elastic fibre network with unusually high levels of branching. The disrupted collagen arrangement seen in adult mgΔ loxPneo mice corneas is likely linked to lower levels of decorin in these corneas.